Topography and distribution of adenosine A2A and dopamine D2 receptors in the human Subthalamic Nucleus - Emmi, Aron; Antonini, Angelo; Sandre, Michele; Baldo, Andrea; Contran, Martina; Macchi, Veronica; Guidolin, Diego; Porzionato, Andrea; De Caro, Raffaele (Frontiers in Neuroscience, 2022)
The human Subthalamic Nucleus (STh) is a diencephalic lens-shaped structure located ventrally to the thalamus and functionally implicated in the basal ganglia circuits. Despite recent efforts to characterize the neurochemical and functional anatomy of the STh, little to no information is available concerning the expression and distribution of receptors belonging to the dopaminergic and purinergic system in the human STh. Both systems are consistently implicated in basal ganglia physiology and pathology, especially in Parkinson’s Disease, and represent important targets for the pharmacological treatment of movement disorders. Here, we investigate the topography and distribution of A2a adenosine and D2 dopamine receptors in the human basal ganglia and subthalamic nucleus. Our findings indicate a peculiar topographical distribution of the two receptors throughout the subthalamic nucleus, while colocalization between the receptors opens the possibility for the presence of A2AR- D2R heterodimers within the dorsal and medial aspects of the structure. However, further investigation is required to confirm these findings.